First-generation medical school applicants: A quantitative study designed to identify areas of educational support - Bethsabe Romero; Amanda K. Burbage (PLoS ONE, 2026)
First-generation (First Gen) students are unique medical school applicants. Due to their lived experience, they approach patient care by prioritizing trust, comfort and understanding. They have proven ability to overcome obstacles and were found to be more resilient than their continuing generation (Cont Gen) peers. Despite these notable attributes, they face unique challenges in gaining medical school acceptance. There are very few quantitative studies examining this student subpopulation, and our study identifies characteristics of first-generation medical school applicants while highlighting areas of needed support. This cross-sectional study used deidentified Application and Matriculating Student Questionnaire survey data that was obtained from the AAMC for 286,656 total applicants for the 2017–2024 period, in which 12.5% identified as First Gen. Descriptive statistics, Mann-Whitney U, independent-samples t - tests, and Chi-square tests were performed to define medical school applicant characteristics, evaluate applicants’ motivations to study medicine, and obstacles to medical school acceptance. All First Gen applicants who reported socioeconomic status (SES) come from low SES backgrounds and are motivated to study medicine by establishing a secure future, eliminating career debt, and affecting social change. First Gen applicants had lower acceptance (43% vs. 57%, p < 0.001) and matriculation rates (42% vs. 56%, p < 0.001). Obstacles to admission include First Gen and low SES statuses, age at matriculation, and time spent in family obligations, each significantly associated with lower acceptance rates (p < 0.001). First Gen medical school applicants and matriculants face disproportionate challenges as they navigate careers in medicine. This diverse group of medical school applicants has much to contribute to the future of medicine. Our study highlights a continued need for academic intervention to reduce barriers in the pre-matriculation stage and throughout medical training for First Gen medical school applicants and matriculants.